Analisis Manajeman Berbasis Sekolah dalam Meningkatkan Mutu Pendidikan Di Sekolah Dasar 2 Ulak Paceh Kabupaten Musi Banyuasin Provinsi Sumatera Selatan - Syahwalan Syahwalan; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Journal on Education, 2024)
This research aims to analyze school-based management in improving the quality of education. Data sources in this research include elementary school principals and teachers. Research data includes in-depth interviews, documents and other supporting data such as literature studies which are used as a basis. Based on the research results, it can be concluded that the implementation of school-based management in improving the The research was carried out at SDN 2 Ulak Paceh, Lawang Wetan District, Musi Banyuasin Regency. quality of education at SDN 2 Ulak Paceh, Lawang Wetan District, Musi Banyuasin Regency is good as seen from; 1) curriculum management where the results achieved by the planned and planned curriculum and its updating are carried out every school year; 2) management of facilities and infrastructure, the results of which were achieved using school operational assistance funds, in addition to obtaining assistance in the form of facilities sourced from the Prabumulih City Education and Culture Office by submitting a proposal first; 3) management of improving teacher quality, where there is an increase in the number of teachers who have teaching certificates every year. Apart from that, to improve the performance of educators, SDN 2 Ulak Paceh, Lawang Wetan District, Musi Banyuasin Regency is trying to complete existing facilities to support learning so that educators can carry out the learning process well; 4) student curriculum, where activities are carried out at SDN 2 Ulak Paceh, Lawang Wetan District, Musi Banyuasin Regency on a scheduled basis, such as flag ceremonies, morning exercise activities for all school members, breakfast together on Fridays and carrying out activities to clean the school environment. This research is important because it provides a clear picture of how SBM can be implemented effectively in improving the quality of education at the primary level. Thus, it is hoped that this research can contribute to literature related to educational management, especially in the context of implementing SBM in elementary schools.